A4NH 2018 annual report highlights: Gender - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2019)
This includes three highlights document for the Gender focus of the CGIAR Research Program on Agriculture for Nutrition and Health: Highlight 1: A Dynamic Portfolio of Gender Research Projects Highlight 2: Setting Priorities for Equity Research in A4NH Highlight 3: Measuring Women’s Empowerment in Agricultural Development Projects